Village Fund Financial Fraud Prevention Model Using Analytical Hierarchy Process Method - Taqi, Muhamad; Ismail, Tubagus; Meutia, Meutia; Sabaruddinsah, Sabaruddinsah; Arifin, Bustanul (Jurnal Organisasi dan Manajemen, 2021)
The objectives of this study are (1). Identify the factors that cause fraud in village fund management in Banten Province (2). Develop a village fund fraud prevention model using the Analytical Hierarchy Process method. Data collection methods were carried out by in-depth interviews and Focus Group Discussion (FGD) by inviting academics and experts. The analysis technique uses the Analytical Hierarchy Process (AHP) to model the prevention of village fund fraud in Banten Province. Findings. The results of this study indicate that the actor who is considered the most dominant in the occurrence of fraud is the Village Head, and the strategy that is considered the most dominant in preventing fraud is to narrow the opportunities. When viewed from the perspective of a strategy to minimize pressure, the most important aspect is the change in external auditors, from a strategy perspective of narrowing opportunities, the most important aspect is to streamline monitoring, then from the perspective of negative rationalization strategies and positive competency strategies, the most important aspects include ethics education moral and management change, and the last aspect of the closeness of the ruler is the most important aspect in the strategy perspective to reduce arrogance.